Pengaruh Price, Online Customer Review, Online Customer Rating Terhadap Keputusan Pembelian Pada Beauty E-commerce SOCO by Sociolla (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2019) - Faza Faiqotuzzahro Rozi; N Rachma; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine the effect of price, online customer review, and online customer rating on purchasing decisions at beauty e-commerce SOCO by Sociolla. This research uses explanatory research with quantitative methods. The population in this study was FEB students of Islamic University Malang class of 2019. The sampling method in this study used purposive sampling technique, in this study sample of 80 respondents via Google form according to the formula used, namely the Malhotra formula. The data analysis in this study uses SPSS 25.0 analytics to test price, online customer review, and online customer rating on purchasing decisions. In this study, price has a significant and partially positive effect on purchase decisions, online customer review have a significant and partially positive effect on purchase decisions, and online customer rating have a significant and partially negative effect on purchase decisions. purchase. acquire. Prices, online customer reviews and online customer ratings have a significant simultaneous influence on purchasing decisions at beauty e-commerce  SOCO by Sociolla. The case study of FEB students at the Islamic University of Malang was 82.1% and the rest was influenced by other variables not included in this study. Keywords: Price, Online Customer Review, Online Customer Rating, And Buying Decisions.